Business models of information and communication enterprises in the conditions of the digital economy - Chukurna, O.P.; Pankovets, L.V. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
The article substantiates the influence of digitalization, which affects the development of socio-economic relations. The trends that arose as a result of the development of digitalization and contribute to the gradual transformation of socio-economic relations and the economic base was identified.Digitization as a factor influencing the change of the economic base was substantiated. The economic basis of business models in the conditions of digitalization is considered. The most widespread business models of the modern type in the conditions of digitalization of the economy was characterized.
Keywords: business models; digital economy; ICT enterprises